ChemInform Abstract: 2, 3‐Diphenylphenanthro[9, 10‐b]furan Derivatives as New Blue Fluorophores. Issue 52 (6th December 2016) - Kojima, Taketo; Kawajiri, Ikumi; Nishida, Jun‐ichi; Kitamura, Chitoshi; Kurata, Hiroyuki; Tanaka, Mirai; Ikeda, Hiroshi; Kawase, Takeshi
Abstract: The key step in the synthesis of the entitled compounds (IV) is an extraordinary Wittig reaction of phenanthrene‐9, 10‐dione (I) and two equivalents of benzylidenetriphenylphosphoranes (II) followed by a dehydrogenation step using DDQ.